Age effects on the development of stimulus over-selectivity are mediated by cognitive flexibility and selective attention. (January 2021) - Kelly, Michelle P.; Reed, Phil
Stimulus over-selectivity is said to have occurred when only a limited subset of the total number of stimuli present during discrimination learning controls behavior, thus, restricting learning about the range, breadth, or all features of a stimulus. The current study investigated over-selectivity of 100 typically developing children, aged 3–7 (mean = 65.50 ± 17.31 SD months), using a visual discrimination task. Developmental trends in over-selectivity and their relationship to some cognitive variables (i.e., selective attention, sustained attention, and cognitive flexibility) were the target. Over-selectivity decreased with age, but this effect was mediated by the development of cognitive flexibility. Over-selectivity increased when a distractor task was introduced, which was not mediated by the other cognitive variables under investigation. The current results assist in the establishment of the theoretical underpinnings of over-selectivity by offering evidence of its underlying determinants and relating these to developmental trends.